All Days 1993
DOI: 10.2118/25166-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New and Reliable Model for Predicting Oilfield Scale Formation

Abstract: A new and reliable Oilfield Scale Prediction Model (OSPMod) has been developed and is presented. Unlike the available models which predict only scaling potential using thermodynamics and limited solubility data, OSPMod predicts the potential and deposition profile based on extensive thermodynamic and kinetic data. The model uses experimental solubility data in NaCl, MgCl2, CaCl2, and their mixtures, and in natural oilfield brines to determine the saturation index. Critical saturation indices beyond which scali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The available models are based on thermodynamics and limited solubility data and can only predict the potential for scale formation. They include the models of Stiff andDavis (1952a, 1952b), Odd0 and Tomson (1982), Valone and Skillern (1982), Vetter and Kandarpa (1980), Vetter et al (1982), Kharaka et al (1988), Atkinson et al (1991), Todd and Yuan (1991), and Yeboah et al (1993).…”
Section: Estimation Of Scale Formation Potentialmentioning
confidence: 99%
“…The available models are based on thermodynamics and limited solubility data and can only predict the potential for scale formation. They include the models of Stiff andDavis (1952a, 1952b), Odd0 and Tomson (1982), Valone and Skillern (1982), Vetter and Kandarpa (1980), Vetter et al (1982), Kharaka et al (1988), Atkinson et al (1991), Todd and Yuan (1991), and Yeboah et al (1993).…”
Section: Estimation Of Scale Formation Potentialmentioning
confidence: 99%
“…Their consequence could be production-equipment failure, emergency shutdown, increased maintenance cost, and an overall decrease in production efficiency. The failure of production equipment and instruments could result in safety hazards [19].…”
Section: The Scaling Problem In Oil Fieldsmentioning
confidence: 99%
“…[14] Common oilfield scales include carbonate and sulphate scales, such as calcium carbonate (CaCO 3 ), calcium sulphate (CaSO 4 Á xH 2 O, CaSO 4 ), and barium sulphate (BaSO 4 ). [15] It is indicated that there are an optimum salinity and multivalent ions concentration in which the amount of mineral scale precipitation is at the minimum level. [16] To reduce the scale formation incidence, scale inhibitors (SIs) are used, which are an effective and inexpensive method compared to mechanical solutions.…”
Section: Introductionmentioning
confidence: 99%